Corporate Practices of Green Human Resources Management - Ardeshir Bazrkar; Ali Moshiripour (Foresight and STI Governance)
Green education and development has a great impact upon improving the environmental performance of companies. Using the example of Iranian small and medium-sized oil and gas enterprises, the article evaluates the practices’ effect on environmental performance. The survey covered 386 employees from 30 companies. The most common measures of green human resources management were analyzed. All these practices have a positive and significant effect on the environmental performance of companies. The action of green education and development was introduced as the most effective measure. The results also demonstrated that four practices of green human resources management have a positive and significant impact upon performance due to environmental knowledge. Companies can use the findings of this research in implementing the green human resources management practices and continuous improvement of the environmental performance.